STUDY ON RALPH WALDOEMERSON’S PROSE IDEALS RESEARCH - Ravi Shankar Prasad (International Journal of Multidisciplinary Research and Studies, 2021)
Ralph Waldo Emerson (1803–82), an American writer, poet, and popular philosopher, began his professional life as a Unitarian pastor in Boston. However, he went on to become a well-known lecturer and the author of such writings as "Self-Reliance," "History," "The Over-Soul," and "Fate." Emerson created a process metaphysics, a mood epistemology, and a "existentialist" self-improvement ethics by drawing on German and English Romanticism, Neoplatonism, Kantianism, and Hinduism. He had an impact on generations of Americans, including his friend Henry David Thoreau, John Dewey, and Friedrich Nietzsche in Europe, who took up topics like power, fate, the uses of poetry and history, and the criticism of Christianity.